Engineered microenvironments for synergistic VEGF – Integrin signalling during vascularization. (May 2017) - Moulisová, Vladimíra; Gonzalez-García, Cristina; Cantini, Marco; Rodrigo-Navarro, Aleixandre; Weaver, Jessica; Costell, Mercedes; Sabater i Serra, Roser; Dalby, Matthew J.; García, Andrés J.; Salmerón-Sánchez, Manuel
Abstract: We have engineered polymer-based microenvironments that promote vasculogenesis both in vitro and in vivo through synergistic integrin-growth factor receptor signalling. Poly(ethyl acrylate) (PEA) triggers spontaneous organization of fibronectin (FN) into nanonetworks which provide availability of critical binding domains. Importantly, the growth factor binding (FNIII12-14 ) and integrin binding (FNIII9-10 ) regions are simultaneously available on FN fibrils assembled on PEA. This material platform promotes synergistic integrin/VEGF signalling which is highly effective for vascularization events in vitro with low concentrations of VEGF. VEGF specifically binds to FN fibrils on PEA compared to control polymers (poly(methyl acrylate), PMA) where FN remains in a globular conformation and integrin/GF binding domains are not simultaneously available. The vasculogenic response of human endothelial cells seeded on these synergistic interfaces (VEGF bound to FN assembled on PEA) was significantly improved compared to soluble administration of VEGF at higher doses. Early onset of VEGF signalling (PLCγ1 phosphorylation) and both integrin and VEGF signalling (ERK1/2 phosphorylation) were increased only when VEGF was bound to FN nanonetworks on PEA, while soluble VEGF did not influence early signalling. Experiments with mutant FN molecules with impaired integrin binding site (FN-RGE) confirmed the role of the integrin binding site of FN on the vasculogenic response via combined integrin/VEGF signalling. In vivo experiments using 3D scaffolds coated with FN and VEGF implanted in the murine fat pad demonstrated pro-vascularization signalling by enhanced formation of new tissue inside scaffold pores. PEA-driven organization of FN promotes efficient presentation of VEGF to promote vascularization in regenerative medicine applications. Graphical abstract: Highlights: VEGF specifically binds to spontaneously formed fibronectin assembled on polymers. Highly efficient VEGF presentation allows simultaneous VEGFR and integrins signalling. Low VEGF amount for endothelial cell reorganization towards primitive vasculature. Fibronectin and VEGF coated PEA scaffold stimulates vessel growth in vivo .